2011
DOI: 10.1128/aem.00665-11
|View full text |Cite
|
Sign up to set email alerts
|

Merging Taxonomy with Ecological Population Prediction in a Case Study of Vibrionaceae

Abstract: We synthesized population structure data from three studies that assessed the fine-scale distribution of Vibrionaceae among temporally and spatially distinct environmental categories in coastal seawater and animals. All studies used a dynamic model (AdaptML) to identify phylogenetically cohesive and ecologically distinct bacterial populations and their predicted habitats without relying on a predefined genetic cutoff or relationships to previously named species. Across the three studies, populations were highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 42 publications
(54 reference statements)
2
66
0
Order By: Relevance
“…Two deep-branching clusters were grouped into a single population by AdaptML, but were treated separately (populations #1 and #2) because of their distinct phylogeny and the fact that #1 was overlapping between years, whereas #2 was observed in 2006 only. We also note that, previously, populations #6, #9, #11 and #14 were listed as members of V. splendidus (Hunt et al, 2008a); however, since then taxonomic revision of populations predicted in our studies has shown that only population #9 is congruent with V. splendidus (though we note that there is disagreement among taxonomists; Le Roux et al, 2009;Preheim et al, 2011b;Supplementary Table 1).…”
Section: Population Prediction and Identification Of 'Projected Habitat'mentioning
confidence: 48%
See 2 more Smart Citations
“…Two deep-branching clusters were grouped into a single population by AdaptML, but were treated separately (populations #1 and #2) because of their distinct phylogeny and the fact that #1 was overlapping between years, whereas #2 was observed in 2006 only. We also note that, previously, populations #6, #9, #11 and #14 were listed as members of V. splendidus (Hunt et al, 2008a); however, since then taxonomic revision of populations predicted in our studies has shown that only population #9 is congruent with V. splendidus (though we note that there is disagreement among taxonomists; Le Roux et al, 2009;Preheim et al, 2011b;Supplementary Table 1).…”
Section: Population Prediction and Identification Of 'Projected Habitat'mentioning
confidence: 48%
“…Sampling during different seasons has revealed strong temporal differentiation with the same 'habitat' type often occupied by season-specific populations (Hunt et al, 2008a;Preheim et al, 2011a). Moreover, two studies carried out 1 year apart but targeting different types of samples from coastal water have suggested population re-occurrence (Preheim et al, 2011b); however, the evidence remains indirect since no sampling scheme has been reproduced in a manner to ascertain to what extent populations occupy the same 'habitats'.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Thus MLSA provides significantly higher resolution. Similar considerations may be obtained from the investigations on the marine planktic genera Synechococcus and Prochlorococcus (Johnson et al 2006) or fine-scale distribution of marine Vibrionaceae (Preheim et al 2011). On the other hand, Kopac et al (2014) analyzed all orthologous genes within Bacillus subtilis and showed that MLSA was insufficient to distinguish ecotypes, which are considered as species in this paper.…”
Section: Species Concept In (Cyano)bacteriamentioning
confidence: 65%
“…MED222, V. parahaemolyticus, and V. fischeri MJ11, and L. anguillarum were obtained from complete genomes available on GenBank. For all other strains, partial sequences were obtained during previous studies using multilocus sequencing (Boucher et al, 2011;Preheim et al, 2011, and references therein). Sequences were aligned using MUSCLE (Edgar, 2004), and manually trimmed before concatenating all alignments.…”
Section: Phylogenetic Analysis and Independent Contrastsmentioning
confidence: 99%